The effect of ploymetric’s training on the percentage of triple jump`s steps and it`s achievement - Khalid, Azad A. (Humanities Journal of University of Zakho, 2018)
The study aimed to identify The effect of ploymetric’s training on the percentage of triple jump`s steps and it`s achievement, which is last (8) week, two times per week. The sample consisted of (32) males, which divided in to two groups control group (16) and experimental group (16). To find the different between pry and posttest , for each group the paired t-test was used .and to find out the different between control and experimental groups the independent t-test was used .the result was the influence of ploymetric’s training was significant on percentage for step , jump and achievement of triple jump for experimental group comparing to control group, and the improvement of percentage was 21.74% for step to 25.80% and 39.22% for jump to 35.66% which resulted to improve the achievement from 9.58m to 10.46 .